Dropshipping Dalam Perspektif Ekonomi Islam - Irdlon Sahil (STAI Syaichona Moh. Cholil Bangkalan, 2019)
This study was intended to explain the dropshipping in the Islamic perspektif.. This method of research is done by reading reference books, journals and other media related to dropshipping. This studies show that dropshipping is a product sale that allows the dropshipper to sell goods to customers by thinking about supplier’s photos or the supplier’s store without having to shovel and sell to customers at a price determined by the dropshipper. Doing Islamic trafficking has illustrated good and proper ordinances so that there’s no harm among humans in making transactions. The legal basis for selling and selling is found in several verses in the Qur’an among them Qs. al-Baqarah:275, Qs. al-Baqarah: 282, Qs. an-Nisa’: 24. Islam allows the dropshipping system to use akad salam, that would be the buying of the goods submitted later on, while the payment was made earlier.